2014
DOI: 10.1017/s146114571400087x
|View full text |Cite
|
Sign up to set email alerts
|

The administration of atomoxetine during alcohol deprivation induces a time-limited increase in alcohol consumption after relapse

Abstract: The administration of selective serotonin reuptake inhibitors (SSRIs) typically used as antidepressants increases alcohol consumption after an alcohol deprivation period in rats. However, the appearance of this effect after the treatment with selective noradrenaline reuptake inhibitors (SNRIs) has not been studied. In the present work we examined the effects of a 15-d treatment with the SNRI atomoxetine (1, 3 and 10 mg/kg, i.p.) in male rats trained to drink alcohol solutions in a 4-bottle choice test. The tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…On the one hand, some preclinical studies have demonstrated reductions in alcohol addiction subsequently to the administration of different 5-HT receptors agonists (Naranjo et al, 1986; Higley et al, 1998; Martijena et al, 2005). On the other hand, the possibility that antidepressant treatment might increase susceptibility to alcoholism has been overlooked (Alén et al, 2013, 2014). Moreover, several clinical studies have shown that pathological gambling, associated with elevated compulsivity, frequently co-occurs with major depression (Cunningham-Williams and Cottler, 2001; Baer et al, 2015; Redden et al, 2015; Agarwal et al, 2016; Grant et al, 2016; Rickelt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, some preclinical studies have demonstrated reductions in alcohol addiction subsequently to the administration of different 5-HT receptors agonists (Naranjo et al, 1986; Higley et al, 1998; Martijena et al, 2005). On the other hand, the possibility that antidepressant treatment might increase susceptibility to alcoholism has been overlooked (Alén et al, 2013, 2014). Moreover, several clinical studies have shown that pathological gambling, associated with elevated compulsivity, frequently co-occurs with major depression (Cunningham-Williams and Cottler, 2001; Baer et al, 2015; Redden et al, 2015; Agarwal et al, 2016; Grant et al, 2016; Rickelt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These therapeutics have drawbacks in that it takes weeks to months for a therapeutic response, and nearly 50% of patients show full remission [1,9]. Moreover, drinking alcohol can potentiate the side effects of antidepressants and worsen the symptoms of depression; for example, reuptake inhibitors can increase alcohol seeking behavior [10,11]. In addition, studies have shown that alcohol can lower the seizure threshold for antidepressants that act as monoamine reuptake inhibitors [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that alcohol can lower the seizure threshold for antidepressants that act as monoamine reuptake inhibitors [12]. Therefore, these limitations make it difficult to treat and manage alcohol withdrawal dependent affective disturbances [13,10].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, authors also found the same effect in animals under combination of AD (escitalopram) and anti-relapse (acamprosate) treatments. Related to that, subchronic treatment with different ADs (SSRIs and SNRIs) has been demonstrated to augment alcohol consumption in animal models of alcohol deprivation, which were treated along abstinence and re-exposed to alcohol selfadministration once AD treatment ended [113,114].…”
Section: Preclinical Evidence Of Antidepressant Treatment Improves Almentioning
confidence: 99%